ID 155 – CO2 versus Nd–YAP lasers: Are they really the same?. Issue 3 (March 2016) - Testani, E.; Pazzaglia, C.; Valeriani, M.
Abstract : Aim of the study: to compare amplitudes and latencies of the laser evoked potentials (LEPs) to CO2 and Nd:YAP laser stimuli. In 6 healthy subjects, A-delta LEPs were acquired using a 32 channel system. CO2 and Nd–YAP laser pulses were delivered on the dorsum of both hands and feet in two sessions. After stimulation of both hand and foot, N2 latency was shorter to CO2 than to Nd:YAP pulses. Only after foot stimulation, P2 latency was significantly shorter with CO2 than Nd–YAP laser. Both N2 and P2 amplitudes to hand and foot stimulation were significantly enhanced in YAP–LEPs, compared to CO2 LEPs. In both CO2 and Nd–YAP LEPs, N1 amplitude to hand stimulation was higher in the contralateral temporal than in the contralateral central trace, even if the difference was not significant. After foot stimulation, N1 amplitudes in the contralateral temporal and central traces were similar. LEP latencies were shorter to CO2 than to Nd–YAP stimulation. With both techniques, hand stimulation produced a higher N1 amplitude in the contralateral temporal trace, while after foot stimulation a N1 component was observed in the both the contralateral temporal and central traces with the same amplitude. These results confirm the N1 origin in the opercular region.